Challenges experienced by newly qualified nurse-midwives transitioning to practice in selected midwifery settings in northern Malawi - Mathews Brave Mtegha; Elizabeth Chodzaza; Ellen Chirwa; Fatch Welcome Kalembo; Maggie Zgambo (BMC, 2022)
Abstract Background Literature shows that newly qualified nurse-midwives face challenges integrating into the workforce during their transition period from education to practice. However, little is known about the needs and challenges of Malawian nurse-midwives during their transition from education to practice. The aim of the study was to explore the transition experiences of newly qualified nurse-midwives working in selected midwifery units in Northern Malawi. Methodology A qualitative descriptive approach was used. Data were collected through in-depth interviews using semi-structured interview guides from a purposive sample of 19 participants (13 newly qualified nurse-midwives and 6 key informants). The researchers developed two interview guides; one for the newly qualified nurse-midwives and another one for the key informants. The interview guides had questions related to newly qualified nurse-midwives experiences of transitioning to practice and the support they received. Participants were from three selected hospitals in the Northern part of Malawi that have maternity units. Data were analysed manually using thematic analysis. Findings Five themes related to challenges faced by newly qualified nurse-midwives during their transition to practice in midwifery units emerged from the thematic analysis of the data. These included (1) Theory-practice gap, (2) Lack of confidence and skills, (3) Inadequate resources, (4) Transition support system, and (5) Workplace conflict. Conclusion Newly qualified nurse-midwives in Malawi encounter many challenges while transitioning from education to practice. The study findings underscore the need to develop a national framework support system that could not only help newly qualified midwives adjust positively to their new role but also create more opportunities for learning and developing and strengthening a collaborative partnership between colleges and hospitals.